Auditory Speech Perception Development in Relation to Patient’s Age with Cochlear Implant - Ciscare,Grace Kelly Seixas (2017)
Abstract Introduction A cochlear implant in adolescent patients with pre-lingual deafness is still a debatable issue. Objective The objective of this study is to analyze and compare the development of auditory speech perception in children with pre-lingual auditory impairment submitted to cochlear implant, in different age groups in the first year after implantation. Method This is a retrospective study, documentary research, in which we analyzed 78 reports of children with severe bilateral sensorineural hearing loss, unilateral cochlear implant users of both sexes. They were divided into three groups: G1, 22 infants aged less than 42 months; G2, 28 infants aged between 43 to 83 months; and G3, 28 older than 84 months.We collectedmedical record data to characterize the patients, auditory thresholds with cochlear implants, assessment of speech perception, and auditory skills. Results There was no statistical difference in the association of the results among groups G1, G2, and G3 with sex, caregiver education level, city of residence, and speech perception level. There was a moderate correlation between age and hearing aid use time, age and cochlear implants use time. There was a strong correlation between age and the age cochlear implants was performed, hearing aid use time and age CI was performed. Conclusion There was no statistical difference in the speech perception in relation to the patient’s age when cochlear implant was performed. There were statistically significant differences for the variables of auditory deprivation time between G3 - G1 and G2 - G1 and hearing aid use time between G3 - G2 and G3 - G1.